1999
DOI: 10.1007/s004250050583
|View full text |Cite
|
Sign up to set email alerts
|

Structure and regulation of the Arabidopsis thaliana allene oxide synthase gene

Abstract: Allene oxide synthase (AOS) is encoded by a single intronless gene in Arabidopsis thaliana (L.) Heynh. The promoter region of the AOS gene exhibits, in addition to the clements of a minimal promoter and the presence of general enhancers, cis-elements that, in other promoters, are responsible for stress- and ethyleneresponsiveness. Arabidopsis thaliana and Nicotiana tabacum L. were transformed with a chimaeric gene consisting of a 1.9-kb 5'-upstream sequence and the first 95 nucleotides of the AOS coding sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 44 publications
(49 reference statements)
5
98
0
5
Order By: Relevance
“…It appears that some defense genes are definitely associated with floral organ abscission in Arabidopsis, whereas others are not so easily detected, or perhaps have not been found yet. Genes encoding chitinases, ␤1-3-glucanases, and jasmonic acid biosynthetic enzymes have been observed to be up-regulated in the abscission zone in response to different stresses (Volko et al, 1998;Kubigsteltig et al, 1999). Chitinases and glucanases are lytic enzymes that are possibly involved in cell wall degradation of many fungi, and promoter-GUS constructs of these genes strongly express in the floral organ abscission zone (Fig.…”
Section: Pathogen-related Genes Associated With Abscissionmentioning
confidence: 99%
“…It appears that some defense genes are definitely associated with floral organ abscission in Arabidopsis, whereas others are not so easily detected, or perhaps have not been found yet. Genes encoding chitinases, ␤1-3-glucanases, and jasmonic acid biosynthetic enzymes have been observed to be up-regulated in the abscission zone in response to different stresses (Volko et al, 1998;Kubigsteltig et al, 1999). Chitinases and glucanases are lytic enzymes that are possibly involved in cell wall degradation of many fungi, and promoter-GUS constructs of these genes strongly express in the floral organ abscission zone (Fig.…”
Section: Pathogen-related Genes Associated With Abscissionmentioning
confidence: 99%
“…Subcellular fractionations in tomato (Lycopersicon esculentum) have indicated that the CYP74A member of this family in tomato is localized on the inner chloroplast membrane facing the stroma and the CYP74B member of this family is localized in the outer chloroplast membrane facing the intermembrane space (Froehlich et al, 2001); other studies simply localize members of this P450 family to the chloroplast without differentiating between its various subcompartments. Biochemically, each of these enzymes has a distinct function with CYP74A (allene oxide synthase [AOS]) members mediating the synthesis of 12-oxo-phytodienoic acid (12-OPDA), jasmonic acid (JA), and its methyl ester (MeJA) from fatty acid hydroperoxide (HP) in the lipoxygenase (LOX) pathway of oxylipin synthesis (Laudert et al, 1996;Laudert and Weiler, 1998;Kubigsteltig et al, 1999) and CYP74B (hydroperoxide lyase [HPL]) members mediating the breakdown of HP to C 6 volatiles and octadecanoic acid (Bate et al, 1998b;Matsui et al, 1999;Fig. 1).…”
mentioning
confidence: 99%
“…"Early genes", i.e., those rapidly induced after wounding, including those encoding prosystemin and some of the JA biosynthetic enzymes, are expressed in vascular bundles (Jacinto et al, 1997;Kubigsteltig et al, 1999;Hause et al, 2000), whereas "late genes", i.e., those for SWRPs with a direct role in plant defense, are expressed in palisade and adjacent spongy mesophyll cells (Shumway et al, 1976;WalkerSimmons and Ryan, 1977;Ryan, 2000). The temporally and spatially separated expression of the two classes of genes led to the suggestion that wound-signaling events may initially be activated in the vascular bundles to produce second messengers (octadecanoids, OGAs, H202) that will then induce defense gene expression in mesophyll cells (Orozco-Cárdenas, 2000;Ryan, 2000).…”
Section: The Role Of Tomato Systemin In Wound Signal Transductionmentioning
confidence: 99%